The immature platelet fraction, a predictive tool for early recovery from dengue-related thrombocytopenia: a prospective study. (9th September 2021) - Abeysuriya, Visula; Seneviratne, Suranjith L; de Mel, Primesh; Clarice, Choong Shi Hui; de Mel, Chandima; Chandrasena, Lal; Yip, Christina; Yap, Eng-Soo; de Mel, Sanjay
Abstract: Background: There is a paucity of predictive factors for early recovery from thrombocytopenia related to dengue. The immature platelet fraction (IPF%) is reflective of megakaryopoiesis and may correlate with recovery from dengue-related thrombocytopenia. Our objective was to assess the predictive value of IPF% on days 2 and 3 of illness for recovery from dengue-related thrombocytopenia. Methods: A prospective study was conducted among patients with dengue admitted to our institution (Nawaloka Hospital PLC) from December 2019 to October 2020. Dengue was diagnosed based on positive non-structural antigen 1 or IgM. IPF% data were extracted from the Sysmex-XN-1000 automated hematology analyzer. Clinical data were obtained from electronic medical records. Statistical analyses were performed using SPSS version 20. Results: We included 240 patients. An IPF% on day 2 of illness of >7.15% had a sensitivity of 80.0% and specificity of 70.4% for prediction of platelet recovery (defined as platelet count ≥60×10 9 /L) on day 7 of illness. An IPF% of >7.25% on day 3 of illness had a sensitivity of 88.9% and specificity of 47.1% for predicting platelet recovery >60×10 9 /L on day 8 of illness. The IPF% was significantly lower in patients with severe dengue. Platelet recovery was observed within 48 h after the peak IPF% was reached, regardless of severity. Conclusion: We propose that IPF% values on days 2 and 3 of illness are a promising predictive tool for early recovery from dengue-related thrombocytopenia.